Bilateral linguofacial trunk - a case report - Shankreppa D Desai; Ashwini B Nuchhi; Santoshkumar B Karjagi (Wolters Kluwer Medknow Publications, 2012)
During routine dissection of an adult male cadaver, a unique case of anomalous origin of linguofacial trunk from both the right and left external carotid arteries with no looping of lingual artery in its course and relative higher division of right common carotid artery at C3 vertebral level was observed. Although variations in the external carotid artery origin and branches are not uncommon it is necessary to document as these variations may increase the risk of accidental vascular trauma during head and neck surgeries. And this knowledge is also important for radiologists in the image interpretation of carotid arterial system.